The Effect of Human Resource Training and Development on Employee Performance in Construction Companies - Nova Yanti Maleha; Aliah Gina; Melis Melis (Sean Institute, 2026)
The construction industry faces tight project schedules, high safety standards, and increasing demands for efficiency and work quality. These challenges require strategic human resource management through effective training and human resource development. This study examines the effects of training and human resource development on employee job performance in a project-based construction company. A quantitative cross-sectional survey was conducted involving all 33 employees of PT Indo Permata Jaya Palembang using a saturated sampling technique. Data were collected through a five-point Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that training has a positive and significant effect on job performance, while human resource development shows a stronger positive and significant influence. Simultaneously, both variables significantly affect job performance, explaining 57.8 percent of its variance. These findings highlight the importance of integrating short-term skill enhancement with long-term capacity building to improve employee performance in construction projects.